Translation and Psychometric Properties of Critical Thinking Scale for Adolescents - Mahwish Masood; Dr. Farah Malik, (Dialogue Social Science Review (DSSR), 2025)
The Critical Thinking Scale is a tool used to measure many aspects of critical thinking, such as analysis, evaluation, inference, interpretation, explanation, and self-regulation. The goal of this study was to translate and examine the psychometric qualities of the scale for teenagers. The scale's validity, reliability, and usefulness for use in evaluating teenagers' critical thinking skills in a secondary school setting were to be ascertained. For the study, a sample of 500 teenagers from Pakistani secondary schools was chosen. Participants were given the Critical Thinking Scale after it was translated into Urdu. Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), correlation analysis, and descriptive statistics were used to analyses the data. Internal consistency was evaluated using Cronbach's alpha, and the scale's structure and measurement fit were confirmed using EFA and CFA. This study translated and evaluated the validity and reliability of the Critical Thinking Skills Scale (CTSS). Forward and backward translation approach developed by Sousa and Rojjanasrirat (2011) used as a research design. 500 adolescents were selected based on convenience sampling and asked to complete the CTSS questionnaire for psychometric testing. We evaluated translation equivalence, the item content validity index, floor/ceiling effects, construct validity, internal consistency reliability and test–retest reliability. The CTSS questionnaire retained the meaning of the original English version and was clear, explicit and easy for adolescent to understand. The Cronbach's alpha was 0.722. The CFA further supported the validity of the scale, with fit indices for most dimensions falling within the acceptable range. Confirmatory factor analysis indicated that this Urdu version fit the proposed model.